Are Muslim immigrants different in terms of cultural integration? - Alberto Bisin; Eleonora Patacchini; Thierry Verdier; Yves Zenou (Institute for the Study of Labor (IZA), 2007)
Using the UK Fourth National Survey of Ethnic Minorities, we explore the determinants of religious identity for Muslims and non-Muslims. We find that Muslims integrate less and more slowly than non-Muslims. A Muslim born in the UK and having spent there more than 50 years shows a comparable level of probability of having a strong religious identity than a non-Muslim just arrived in the country. Furthermore, Muslims seem to follow a different integration pattern than other ethnic and religious minorities. Specifically, high levels of income as well as high on-the-job qualifications increase the Muslims' sense of identity. We also find no evidence that segregated neighborhoods breed intense religious and cultural identities for ethnic minorities, especially for Muslims. This result casts doubts on the foundations of the integration policies in Europe.
Keywords: 300; Einwanderung; Migranten; Islamisch; Soziale Integration; Großbritannien